Pesticide residues in nectar and pollen of melon crops: Risk to pollinators and effects of a specific pesticide mixture on Bombus terrestris (Hymenoptera: Apidae) micro-colonies. (1st June 2023) - Azpiazu, Celeste; Medina, Pilar; Sgolastra, Fabio; Moreno-Delafuente, Ana; Viñuela, Elisa
Abstract: Residues detected in pollen collected by honey bees are often used to estimate pesticide exposure in ecotoxicological studies. However, for a more accurate assessment of pesticides effect on foraging pollinators, residues found directly on flowers are a more realistic exposure approximation. We conducted a multi-residue analysis of pesticides on pollen and nectar of melon flowers collected from five fields. The cumulative chronic oral exposure Risk Index (RI) was calculated for Apis mellifera, Bombus terrestris and Osmia bicornis to multiple pesticides. However, this index could underestimate the risk since sublethal or synergistic effects are not considered. Therefore, a mixture containing three of the most frequently detected pesticides in our study was tested for synergistic impact on B. terrestris micro-colonies through a chronic oral toxicity test. According to the result, pollen and nectar samples contained numerous pesticide residues, including nine insecticides, nine fungicides, and one herbicide. Eleven of those were not applied by farmers during the crop season, revealing that melon agroecosystems may be pesticide contaminated environments. The primary contributor to the chronic RI was imidacloprid and O. bircornis is at greatest risk for lethality resulting from chronic oral exposure at these sites. In the bumblebee micro-colony bioassay, dietary exposure to acetamiprid, chlorpyrifos and oxamyl at residue level concentration, showed no effects on worker mortality, drone production or drone size and no synergies were detected when pesticide mixtures were evaluated. In conclusion, our findings have significant implications for improving pesticide risk assessment schemes to guarantee pollinator conservation. In particular, bee pesticide risk assessment should not be limited to acute exposure effects to isolated active ingredients in honey bees. Instead, risk assessments should consider the long-term pesticide exposure effects in both pollen and nectar on a range of bees that reflect the diversity of natural ecosystems and the synergistic potential among pesticide formulations. Graphical abstract: Image 1 Highlights: Nineteen pesticides were detected, eleven of them had not been applied in the crops Imidacloprid was the main contributor in the cumulative chronic risk index Mason bees have the greatest risk of lethality associated with chronic oral exposure Residue dose of one frequently mixture did not affect bumblebee micro-colonies